Integration of Next Generation IIoT with Blockchain for the Development of Smart Industries - Aamir Iqbal; Mohammad Amir; Vinod Kumar; Aftab Alam; Mohammad Umair (Emerging Science Journal, 2020)
In modern era, a wide range of smart industries is being focus on automation-based applications. Various technologies are rapidly implementing in Industrial Internet of Things (IIoT) for manufacturing sectors that helping to achieve advanced schedule production framework and on time delivery of products. The integration of IIoT platforms with the blockchain are challenging service in manufacturing system. The primary objective of this article is to characterize various issues and challenges that are implementing IIoT and blockchain in industries. The proposed work is an integration of IIoT and blockchain in industrial processes for solving the security issues in real-time. Also, identifying various enablers of blockchain and issues of IIoT from smart industries manufacturing using a survey tool is formed in the form of questionnaire. Based on these responses Decision Making Trial and Evaluation Laboratory (DEMATEL) technique has been implemented for categorizing these challenges into cause and effect. In this paper, we introduce the general layout with their key issues and challenges of IIoT and blockchain that signifies the safety requirements to design the IIoT and blockchain. Further, we describe how IIoT can be integrated to the blockchain for smart Industrial applications. Finally, various recommendations are the proposed to upcoming IIoT and blockchain developments. The proposed work will be highly beneficial for the smart industries to develop a next generation IIoT and blockchain based framework.